Empirical analysis of the impact of Turkish bilateral official development assistance on export - Arab Dahir Hassan; Esra Dil (Economic Journal of Emerging Markets, 2023)
Purpose ― The main objective of this study is to explore the relationship between bilateral official development assistance and the export of Turkey to 18 Turkish aid recipient countries between 1998 and 2019. Methods ― The study employs the gravity model of international trade to capture the effect of official development assistance on Turkish export to its aid recipient countries and utilizes Panel data econometric analysis. Findings ― The official development assistance (ODA) remains statistically significant across the models, indicating that ODA is one of the significant drivers of Turkish bilateral trade with the aid recipient countries. Implications ― The study argues that Turkey applied ODA as a foreign policy tool to access new markets in the Middle East, Balkans, Africa, and Asia. Turkish exports to developing countries increased due to the upsurged country's foreign aid donation to its recipients. Originality ― This study deviates from other studies in the literature by empirically examining the relationship between bilateral Official development assistance and the export of Turkey.